ORGANIZATIONAL MANAGEMENT OF DIGITAL-BASED ARABIC LANGUAGE COURSES - Jannah, Mawaddatul; Mufidah, Nuril (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2025)
Organizational management plays a crucial role in ensuring the effectiveness of educational program implementation, particularly in digital-based learning institutions. This study aimed to describe the organizational management practices of a digital Arabic language course at Arabiyahtalks Academy, focusing on program management strategies and the division of tasks within its organizational structure. A descriptive qualitative approach was employed. Data were collected through observations of the official Instagram account @arabiyahtalks, in-depth interviews with the director and program tutors, and supporting documentation. The data were analyzed using the Miles and Huberman model, which involved data reduction, data display, and conclusion drawing. The findings showed that Arabiyahtalks Academy implemented digital-based management by utilizing platforms such as Google Meet for instruction and Instagram (through feed content, microblogs, and carousels) for promotion and audience engagement. Learning evaluations were conducted using the Kahoot platform. The organizational structure included a clear division of tasks, such as formulating vision and goals, recruiting instructors, developing marketing strategies, and grouping classes based on learners’ proficiency levels.